Shifting cultivation and soil conservation strategies among Papuan communities, Indonesia - MAHMUD MAHMUD; SRI ENDAYANI; ANDREW STEFANO; AMALIA LAKEHU; MUTAKIM MUTAKIM; WAHYUDI WAHYUDI; SUSILO BUDI HUSODO; SOETJIPTO MOELJONO (Asian Journal of Agriculture, 2025)
Abstract. Mahmud, Endayani S, Stefano A, Lakehu A, Mutakim, Wahyudi, Husodo SB, Moeljono S. 2025. Shifting cultivation and soil conservation strategies among Papuan communities, Indonesia. Asian J Agric 9: 671-682. Local Papuan communities in Indonesia, rely heavily on land resources for food security, yet shifting cultivation remains the dominant practice. This system, while traditional, often leads to soil nutrient depletion, reduced productivity, and increased deforestation. To understand the dynamics of local farming practices, this study applied interviews, surveys, and participatory approaches with farmers and community members. Findings reveal that short-term crops such as long beans, peanuts, cabbage, chilies, and sweet potatoes dominate cultivation, contributing to rapid soil fertility loss. In contrast, perennial crops such as Areca catechu, Musa paradisiaca, Nephelium lappaceum, and Artocarpus altilis are typically maintained in fixed plots without being shifted. To address soil degradation, the study proposes several conservation strategies. These include mulching to retain soil moisture, living fences and cover crops to minimize erosion, intercropping to diversify yields and improve nutrient cycling, and the integration of Multipurpose Tree Species (MPTS) and hedgerows to restore long-term soil fertility. Collectively, these measures can reduce the necessity for continuous land clearing and help communities move toward more sustainable sedentary agricultural systems. Beyond technical solutions, the research highlights the importance of strengthening community awareness about forest and soil conservation. Transitioning away from shifting cultivation not only improves land productivity but also contributes to broader ecological resilience. By adopting integrated conservation practices, Papuan farmers can secure food production, maintain forest ecosystems, and develop more sustainable livelihoods in harmony with their environment.